Child Perpetrators of Drug Crimes: Legal Protections and Effectiveness in Indonesian Juvenile Justice - Hasnah Aziz; Imam Rahmaddani; Kuntadi Kuntadi (APPTHI, 2022)
Abstract. The widespread prevalence of drug abuse has reached various segments of society, penetrating even remote villages and influencing children whose cognitive abilities are still developing and are easily susceptible. This research aims to achieve two objectives: firstly, to investigate and analyze legal protection efforts for children involved in drug abuse, and secondly, to understand and analyze the forms of legal protection within the juvenile justice system. The study adopts a Juridical Normative approach with a descriptive analytical research specification, outlining the relevant legislation in connection with legal theories and the practical implementation of positive law related to issues concerning children involved in drug abuse. The research consists of two stages in library research and field research. Conclusions are drawn using a qualitative juridical normative method. The findings indicate that, firstly, legal protection efforts for children can take the form of safeguarding their freedom and fundamental rights. In the context of child protection in Indonesia, Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection has been enacted. To protect children from drug abuse, Indonesia has also implemented Law No. 35 of 2009 concerning Narcotics. Secondly, the forms of protection provided to children as perpetrators of drug abuse crimes within the juvenile criminal justice system in Indonesia, based on Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, allow for the processing of any child committing a criminal act through the legal process, including children involved in drug abuse, who may undergo formal criminal justice proceedings. Abstrak. Penyalahgunaan narkoba yang merajalela telah mencapai berbagai lapisan masyarakat, bahkan menembus desa-desa terpencil dan memengaruhi anak-anak yang kemampuan kognitifnya masih berkembang dan mudah terpengaruh. Penelitian ini bertujuan untuk mencapai dua tujuan: pertama, untuk menyelidiki dan menganalisis upaya perlindungan hukum bagi anak-anak yang terlibat dalam penyalahgunaan narkoba, dan kedua, untuk memahami dan menganalisis bentuk perlindungan hukum dalam sistem peradilan pidana anak. Penelitian ini mengadopsi pendekatan Normatif Yuridis dengan spesifikasi penelitian analitis deskriptif, menguraikan perundang-undangan yang relevan terkait teori-teori hukum dan implementasi praktis hukum positif yang berkaitan dengan masalah anak-anak yang terlibat dalam penyalahgunaan narkoba. Penelitian ini terdiri dari dua tahap, yaitu penelitian kepustakaan dan penelitian lapangan. Kesimpulan diambil dengan menggunakan metode normatif yuridis kualitatif. Temuan menunjukkan bahwa, pertama, upaya perlindungan hukum bagi anak dapat berbentuk menjaga kebebasan dan hak-hak dasar mereka. Dalam konteks perlindungan anak di Indonesia, telah diberlakukan Undang-Undang Nomor 35 Tahun 2014 tentang Perubahan atas Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak. Untuk melindungi anak-anak dari penyalahgunaan narkoba, Indonesia juga menerapkan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika. Kedua, bentuk perlindungan yang diberikan kepada anak sebagai pelaku tindak pidana penyalahgunaan narkoba dalam sistem peradilan pidana anak di Indonesia, berdasarkan Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak, memungkinkan pemrosesan anak yang melakukan tindak pidana melalui proses hukum, termasuk anak-anak yang terlibat dalam penyalahgunaan narkoba, yang mungkin menjalani proses peradilan pidana formal. Kata kunci: Anak, Penyalahgunaan narkoba, Peradilan anak, Perlindungan hukum, Narkotika